Identifikasi Kompetensi Sumberdaya Manusia di desa Wisata Kereng Bangkirai dalam Pengembangan Wisata Berkelanjutan (Studi Kasus Pemahaman Pengelolaan Pariwisata Berkelanjutan) - Rabeka Putri; Amelda Pramezwary (CV. Creative Tugu Pena, 2024)
Community participation in tourism development in Kereng Bangkirai Village is crucial, despite challenges such as the limited understanding of sustainable tourism concepts among the human resources in the village. This research aims to explore the understanding of human resources, particularly the managers of Kereng Bangkirai Village and selected community members, regarding sustainable tourism. Utilizing a qualitative approach with descriptive qualitative methods, the research gathered primary data through interviews and observations, while secondary data were obtained from literature reviews and other references. The findings indicate that the competence of human resources in Kereng Bangkirai Village for sustainable tourism development faces crucial challenges. Understanding, management skills, and the attitudes and behaviors of the community vary. Internal factors, such as motivation and interests, influence competence, while external factors, including the environment and collaboration with the government, also play a significant role. Challenges include a lack of understanding of sustainable tourism concepts, weak skills, and variations in community attitudes. A synergy between internal and external factors is essential to overcome barriers and advance the development of sustainable tourism in the village.